Recent approaches to novel anti-Alzheimer therapy - Carreiras, MC (2015)
Insufficient cholinergic neurotransmission in AD is responsible for a progressive loss of cognition and motor capacities. The cholinergic hypothesis has provided the rationale for the current treatment approaches based on acetylcholinesterase inhibitors. However, recent data focus on the complex nature of AD and disclose the involvement of other neurotransmitters such as serotonin, noradrenalin, dopamine, histamine, excitatory amino acids and neuropeptides among others. Interestingly, recent research has revealed that in severe AD brains the levels of AChE are considerably reduced whereas BuChE activity increases, thus aggravating the toxicity of betaA. In such instances, it is possible that BuChE may be a more suitable target than AChE. Oxidative stress has been implicated in CNS degenerative disorders such as AD and PD. Therefore, owing to their capacity to inhibit oxidative damage, MAOIs are potential candidates as anti-Alzheimer drugs. More recently, a novel drug - TV3326 - was designed, based upon two pharmacophores: the carbamate moiety from rivastigmine, an AChE inhibitor; and the propargyl group from rasagiline, a MAO inhibitor. This drug exhibits cholinesterase and selective brain MAO inhibitory activities, reduces apoptosis and stimulates the processing of APPalpha, hence reducing the possibility of generation of the toxic betaA. Thus, TV3326 may be expected to contribute positively to the cognitive benefits of Alzheimer's patients. Anyhow, the development of drugs with several targets and diverse pharmacological properties may conclusively demonstrate the most beneficial therapy.